Objektivierung des Schwingungskomforts schwerer Nutzfahrzeuge - Bulthaupt, Nils (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
A time efficient development process of new trucks includes an early development of ride comfort before real prototypes exist. Therefore it is necessary to determine objective and measurable characteristic values to predict the subjectively percepted ride comfort from measurement or simulation results. The aim of this work is the determination of objective characteristic values for three selected vibration phenomena and the prediction of their subjective evaluations.